Novel MT-ND Gene Variants Causing Adult-Onset Mitochondrial Disease and Isolated Complex I Deficiency - Ng, Yi Shiau; Thompson, Kyle; Loher, Daniela; Hopton, Sila; Falkous, Gavin; Hardy, Steven A.; Schaefer, Andrew M.; Shaunak, Sandip; Roberts, Mark E.; Lilleker, James B.; Taylor, Robert W. (Frontiers in Genetics, 2020)
Mitochondrial complex I deficiency is associated with a diverse range of clinical phenotypes and can arise due to either mitochondrial DNA (mtDNA) or nuclear gene defects. We investigated two adult patients who exhibited non-syndromic neurological features and evidence of isolated mitochondrial complex I deficiency in skeletal muscle biopsies. The first patient presented with indolent myopathy, progressive since age 17, while the second patient developed deafness around age 20 years and other relapsing-remitting neurological symptoms since. A novel, likely de novo, frameshift variant in MT-ND6 (m.14512_14513del) and a novel maternally-inherited transversion mutation in MT-ND1 were identified, respectively. Skewed tissue segregation of mutant heteroplasmy level was observed; the mutant heteroplasmy levels of both variants were greater than 70% in muscle homogenate, however, in blood the MT-ND6 variant was undetectable whilst the mutant heteroplasmy level of the MT-ND1 variant was low (12%). Assessment of complex I assembly by Blue-Native PAGE demonstrated a decrease in fully assembled complex I in the muscle of both cases. SDS-PAGE and immunoblotting showed decreased levels of mtDNA-encoded ND1 and several nuclear encoded complex I subunits in both cases, consistent with functional pathogenic consequences of the identified variants. Pathogenicity of the m.14512_14513del was further corroborated by single-fibre segregation studies.